Swimming and the development of children and adolescents with Autism Spectrum Disorder (ASD) (Research, Society and Development, 2025)
This study aimed to analyze, through a literature review, the effects of swimming on the motor, social, and behavioral development of children and adolescents with Autism Spectrum Disorder (ASD). A search was conducted in the BVS database using specific descriptors, which initially resulted in 28 records. After screening and applying inclusion and exclusion criteria, 10 articles were selected for the final analysis. The results highlighted consistent benefits of aquatic practice, such as improvements in basic motor skills, pool entries and exits, breathing control, and water safety. From a behavioral and social perspective, swimming was associated with reduced stereotypies, enhanced social interaction, and improved social competence. Additionally, positive impacts on physiological aspects such as sleep quality and overall well-being were reported. Some studies also emphasized the importance of professional training for instructors in order to maximize the effectiveness of aquatic interventions. It is concluded that swimming is an effective and inclusive strategy that promotes integral development, autonomy, and quality of life in children and adolescents with ASD, although more robust studies are required to consolidate these findings.